Fostering autonomous motivation, physical activity and cardiorespiratory fitness in rheumatoid arthritis: protocol and rationale for a randomised control trial - Rouse, P.; Veldhuijzen van Zanten, J.; Metsios, G.; Ntoumanis, Nikos; Yu, C.; Koutedakis, Y.; Fenton, S.; Coast, J.; Mistry, H.; Kitas, G.; Duda, J. (Biomed Central Ltd, 2014)
Background: People with rheumatoid arthritis are at greater risk of morbidity and mortality from cardiovascular disease than the general population. Sustained physical activity increases cardio-respiratory fitness and reduces cardiovascular disease risk factors. However, little is known about how we can effectively promote long-term participation in physical activity in patients with rheumatoid arthritis. The literature consistently calls for physical activity interventions, and their implementation, to be theoretically-grounded. Methods/Design: This paper documents the protocol of a randomised control trial that investigates whether a Self-determination Theory-based intervention fosters the adoption and maintenance of physical activity (3, 6 and 12 months) sufficient to provide sustained cardiovascular and personal well-being benefits in patients with rheumatoid arthritis. The cost effectiveness of the intervention will also be determined. The trial is registered as Current Controlled Trials ISRCTN04121489. Discussion: Results from this trial will provide guidance regarding key social environmental factors that can be manipulated to support motivational processes conducive to positive health behaviour change and optimal functioning in patients with Rheumatoid Arthritis.